1600 AD Huaynaputina Eruption (Peru), Abrupt Cooling, and Epidemics in China and Korea. (27th December 2015) - Fei, Jie; Zhang, David D.; Lee, Harry F.
Abstract : The 1600 AD Huaynaputina eruption in Peru was one of the largest volcanic eruptions in history over the past 2000 years. This study operated on the hypothesis that this event dramatically affected the weather and environment in China and the Korean Peninsula. Over the course of this research the Chinese and Korean historical literatures as well as dendrochronology records were examined. The historical evidence points to the conclusion that the eruption was followed by an abrupt cooling period and epidemic outbreaks in 1601 AD within both China and the Korean Peninsula. These records manifested themselves in unseasonably cold weather resulting in severe killing frosts in northern China in the summer and autumn of 1601 AD. In southern China (Zhejiang and Anhui Provinces and Shanghai Municipality), July was abnormally cold with snow, with an autumn that saw anomalously hot weather. In addition, there was unseasonable snowfall that autumn within Yunnan Province. Widespread disease outbreaks occurred in August, September, and October in northern and southern China. In Korea, the spring and early summer of 1601 AD were unusually cold, and conditions led to further widespread epidemics occurring in August.